Necropapiloscopy: A variant of the Dorrego method (2019)
Introduction: In 1969 the then First Officer of the Argentine Federal Police, José Hipólito Dorrego, devised a technique for the identification of mummified bodies. A methodology based on that technique is proposed, varying the final support whilst taking the fingerprints. Materials and methods: First, the Dorrego doll is shaped (a piece of plasticine is wrapped in latex or nylon gloves), and inked. Once the hand tissue is dry, it is inked by being pressed against the aforementioned Dorrego doll. It is then, in turn, pressed with medium intensity against the adhesive side of some transparent tape. This will capture the papillary relief. It is then detached carefully so as to not damage the tissue and is transferred by gluing it to a transparent acetate. Finally, the papilloscopic confrontation or its loading to the AFIS / SAID, is carried out by using the mirror image of the acetate. Results and discussion: It is possible to considerably increase the quality of the imprint in integrity (field of papillary drawing) and sharpness (differentiation of interpapillary ridges / grooves). In addition, the method was viable for other cadaveric states (emphysematous and carbonized), as long as the tissue is previously dry. Further experimentation should be carried out on the inner side of the epidermis and especially on the ever-delicate dermis.Conclusions: With this variant, the cost and time required for necropapillary identification is reduced while also multiplying and optimizing the number of suitable imprints per inking.